Perbandingan Urusan Metrologi Legal Indonesia dan Belanda - Dine Evantara; Irfan Ridwan Maksum (Universitas Medan Area, 2019)
Indonesia Netherlands has a historical background regarding the implementation of Legal Metrology in Indonesia, starting with the Tera Ordinance in 1923. The implementation of legal metrology at that time was centralistic. The Enactment of Law number 23 of 2014 regarding Regional Government replaced the old regional government law transfer the authority of legal metrology from the Province to the Municipality/City. The role of legal metrology in national economic development through harmonization of standards and technical requirements of legal metrology one standard one test accepted everywhere in bilateral, regional and international trades levels. The research aim to find out how the comparison of legal metrology matters held in Indonesia and Netherland. Legal Metrology affairs in the Netherlands is held by the central government (centralized) with private partnership that has been verified by Welmec the European Legal Metrology in the process of services, re-services, supervision, while in Indonesia the matter of legal metrology is decentralized into the authorithy of the Regency/City which currently has many obstacles in terms of human resources, infrastructure, financing and awareness of the Regional Head and DPRD.